Application of Physics Infographic Learning Media to Student Graphic Interpretation Ability at Straight Motion Topic - Nurfadhilah Nurfadhilah; Khaeruddin Khaeruddin; Usman Usman (Universitas Lambung Mangkurat, 2023)
This research is a descriptive and quantitative study to know students' graphic interpretation ability after applying infographic learning media to learning physics in straight-motion material at MA DDI Kanang. The type of research is pre-experimental with a one-shot case study research design. The independent variable of the research was infographic media, and the dependent variable was students' ability to interpret graphs. The population in this study consisted of 45 class X MIPA students at MA DDI Kanang. Research data were obtained by giving objective tests or multiple choice questions based on four indicators of graph interpretation capability: determining the value of a certain quantity from the graph, translating graphic language into verbal language, identifying graphics based on descriptions, and identifying graphs with different variables. Based on the results of descriptive data analysis using the SPSS application, it was found that the average score of students' graphic interpretation skills at MA DDI was 9.04 and was in the moderate category. The impact is that students can only interpret simple graphs, and have difficulty comparing graphs with various variables.